PENGARUH KUALITAS AKTIVA PRODUKTIF DAN TINGKAT SUKU BUNGA KREDIT TERHADAP KEUNTUNGAN BANK - Ardiasturti, Riska (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2010)
The purpose of this study is to determine the effect of the proportion of quality in earning assets and interest rates of loans to bank profitability that listed in Indonesia Stock Exchange (BEI). The independent variables in this study is the quality in earning assets and interest rates on credit. Both of these variables investigated by partial effects (individual) and simultaneously (shared) to the dependent variable is profitability. Data from each variable were taken with the technical documentation by the end of the period during the years 2003-2008. Analisis technique uses multiple linear regression. From the whole analysis can be concluded that the greater the quality in earning assets and interest rates on loans will be greater the profitability of a bank.